International Sanctions against Iran under President Ahmadinejad: Explaining Regime Persistence - Oliver Borszik (German Institute of Global and Area Studies (GIGA), 2014)
This paper seeks to explain how Iran's regime persisted in the face of international sanctions during Mahmud Ahmadinejad's presidency, from 2005 to 2013. It reconstructs the interplay between the intensifying UNSC, US and EU sanctions and the targeted regime's strategies to advance the nuclear program and maintain intra-elite cohesion. Initially, the nuclear program was expanded due to high oil income in combination with explicit resistance to the presumed regime-change ambitions of the Western sanction senders. At the end of Ahmadinejad's presidency, the decline of foreign exchange earnings from oil exports and the continued regime-change scenario contributed to the neglect of this regimelegitimizing strategy in favor of the maintenance of intra-elite cohesion. My main argument is that once the US and EU oil and financial sanctions curtailed the cost-intensive further development of the nuclear program, Supreme Leader Ali Khamenei used these sanctions as an external stimulus to contain burgeoning factional disputes.
Keywords: 300; Iran; international sanctions; authoritarian regimes; nuclear strategy; factional disputes